Exact and approximation algorithms for sensor placement against DDoS attacks - Junosza-Szaniawski, Konstanty; Nogalski, Dariusz; Rzążewski, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
In a distributed denial of service (DDoS) attack, the attacker gains control of many network users through a virus. Then the controlled users send many requests to a victim, leading to its resources being depleted. DDoS attacks are hard to defend because of their distributed nature, large scale and various attack techniques. One possible mode of defense is to place sensors in a network that can detect and stop an unwanted request. However, such sensors are expensive, as a result of which there is a natural question as to the minimum number of sensors and their optimal placement required to get the necessary level of safety.
Keywords: DDoS; sensor placement; network safety optimization; heuristics